EKSISTENSI FRAKSI DI DPRD DALAM SISTEM LEMBAGA PERWAKILAN BERDASARKAN UU N0 17 TAHUN 2014 TENTANG MD3 - M. Saleh; H. Abdul Khair; Kafrawi Kafrawi; Sarkawi Sarkawi (Universitas Mataram, 2021)
The purpose of this study is to see the strengthening of factions in the DPRD, both institutionally and normatively. The research method used to achieve this goal is to use a normative research method with a legislative approach, a conceptual approach and a historical approach, by examining more specifically about regulatory and institutional strengthening of factions in the DPRD. With this research, it is hoped that there will be further institutional strengthening and normalization of the law regarding the position of legislative institutions in the regions. So far, the existence of factions in the DPRD based on existing laws is not included as a complement to the Council.